GC–MS analysis of the designer drug α-pyrrolidinovalerophenone and its metabolites in urine and blood in an acute poisoning case - Grapp, Marcel; Sauer, Christoph; Vidal, Christian; Müller, Dieter (Forensic science international, 2016)
•We report a case of severe poisoning with α-pyrrolidinovalerophenone (α-PVP).•α-PVP and its 2″-oxo-metabolite were identified in urine by GC–MS.•The concentration of α-PVP was determined in serum.•The presented data were linked to the clinical condition excited delirium syndrome. α-Pyrrolidinovalerophenone (α-PVP) is a synthetic cathinone belonging to the group of “second generation” pyrrolidinophenones that becomes more and more popular as a designer psychostimulant. Here we provide toxicological analytical support for a severe poisoning with α-PVP. Serum and urine samples that were sent to our laboratory were subjected to a general unknown screening procedure. The procedure includes immunoassay-based screening of drugs of abuse in serum and systematic toxicological analysis of urine and serum after neutral and basic liquid–liquid extraction followed by gas chromatography–mass spectrometry (GC–MS). Whereas the immunoassay delivered negative results, analyzing the urine sample by GC–MS in full scan mode disclosed the presence of α-PVP and its metabolites α-(2″-oxo-pyrrolidino)valerophenone (2″-oxo-α-PVP) and 1-phenyl-2-(pyrrolidin-1-yl)pentan-1-ol (OH-α-PVP). In the acetylated urine sample we found additionally N,N-bis-dealkyl-PVP. In serum, α-PVP could be detected after solid phase extraction and a concentration of 29ng/mL was determined. Other forensic relevant substances were not detected. The presented data can explain the psychotic symptoms and behavioural pattern of the subject after abuse of α-PVP, leading to a clinical condition similar to excited delirium syndrome.